Gadget & adolescent: Its effect depiction on the daily life - Herdianto, Roni; Syahidin , Dzikra (Bulletin of Social Informatics Theory and Application, 2020)
Adolescence and gadget are inseparable these days. This research aimed at describing the characteristics of gadget user and social-religious aspect influence. This research employed a descriptive qualitative method. The researchers took a role as an observer dan data collector. This research was conducted on Junior High School X. It took 39 male students as the subject. The data collection was done by distributing the questionnaire. The questionnaire consisted of 14 items. The data obtained were arranged based on the discussion category. The findings explained: (1) the characteristics of adolescences in Junior High School X as the gadget user, gadget ownership characteristics, usage duration, how to obtain internet access, internet use, the most used application; (2) the influence of gadget use on the social life such as pornographic content, social interaction, studying concentration, and religious aspect of the adolescence. This research concludes that, based on the characteristics of the users, the gadget provides both negative and positive impacts. Furthermore, it is important to have attention and guidance by the related stakeholders to be concerned about the mental health of the adolescence as well as the social-religious aspects.